Inseason crop yield forecasting for early warning planning of food security using CCAFS Regional Agricultural Forecasting Toolbox (CRAFT) in Nepal - Gyawali, Dhiraj Raj; Shirsath, Paresh Bhaskar; Kanel, Damodar; Burja, Kurt; Arun, K.C.; Aggarwal, Pramod K.; Hansen, James W.; Rose, Alison (2018)
The unpredictability of crop yields in climate vulnerable regions is damaging in many ways, negatively impacting food security as well as imports, exports, food prices, and people’s livelihoods. The CCAFS Regional Agricultural Forecasting Toolbox (CRAFT) is an open source, flexible crop-forecasting platform that includes a crop simulation module, a weather and seasonal forecast simulation module, and a geographic information system module. The toolbox aims to provide information to ensure better management of agricultural risks associated with increased climate variability and extreme weather events. It uses historical databases of weather and crop yields and current weather to estimate yields of various crops. Advances in crop forecasting technology and crop modelling help with the estimation of inseason crop yields under a variable climate, which enables stakeholders such as policy makers, line agencies, cooperatives, extension workers, and farmers to better prepare the mitigation strategies to cope with risks. From November 2014 through December 2016, CRAFT was implemented in Nepal to forecast yields of wheat and paddy; forecast levels aligned closely with Ministry estimates. Currently, CRAFT is being tested for yield forecasting at the sub-national level in Nepal. The main objective of this paper is to present the status and performance of CRAFT for food security monitoring in Nepal. It presents the data inputs, the methodology and structure of the model, results and performance, limitations, and assumptions made in forecasting the yields of paddy and wheat for different seasons in Nepal.